Influence of Molybdenum Content and MoOxy- Species on the Textural and Structural ZrO2 Properties. (18th December 2014) - Zapién, Alberto Hernández; Enríquez, Juan Manuel Hernández; Alamilla, Ricardo García; Robles, Guillermo Sandoval; García, Ulises Páramo; Serrano, Luz Arcelia García
Abstract : The present work proposes to study the incorporation of molybdenum into the zirconium oxide precursor (Zr(OH)4 ), in order to analyze its possible repercussions on the textural and structural zirconia properties (ZrO2 ). For this, the Zr(OH)4 was synthesized by the sol-gel method and modified with 5, 10, and 15 wt% of molybdenum into the stabilized oxide. The synthesized materials were dried at 120°C for 24 h and then were calcined at 600°C for 3 h. The characterization of the solids was carried out by thermal analysis, X-ray diffraction, nitrogen physisorption, infrared spectroscopy, and scanning electron microscopy. The thermal analyses results showed that the change from the amorphous to the crystalline phase of ZrO2 is shifted to higher temperatures due to the presence of molybdenum content. Tetragonal phase was identified for all synthesized materials, showing a decrease in crystallinity as a function of the metal content. The textural properties were improved due to the incorporation of molybdenum into the ZrO2 structure, developing specific surface areas which are above up to four times the area of pure ZrO2 . The synthesized materials presented spherical morphology with particle sizes less than 1  µ m, with a change of this morphology for high metal contents (15 wt%) being observed.